ANALISIS KESTABILAN AERODINAMIKA PADA RUDDER PESAWAT TERBANG N2XX PADA KONDISI LEFT ENGINE INOPERATIF (LEI) - Exwan Rahmawan; Gaguk J atisukamto (ROTOR, 2017)
Airplane stability is required when the aircraft has a left engine in operative (LEI). LEI is the condition of the left engine part of the aircraft not functioning when flying or taking off. The LEI can be anticipated by using a rudder as support. The purpose of this study was to determine the aerodynamic characteristics of the rudder. The research methodology is by rudder aerodynamic analysis using Datcom digital software simulation. The simulation input data consists of: coefficient of yowing deflection of debt (CNDR) = -0.0022889 / deg, and Vertical Volume (Vv) = 0.0830. Previous tests used VV = 0.79 and then VV = 0.83. The results showed that the number Vv = 0.83 was more stable compared to Vv = 0.79. The research conclusions are that if the plane experiences an LEI, then the stability of the rudder is conditioned as follows: Vv = 0.083, CNDR = -0.0022889 / degree, lift coefficient CL = 1.8837 and angle of attack (α) = 8.3277. Keywords: Left engine in operative, vertical volume, Digital Datcom, Angle of attack